Embracing singlehood experience: A phenomenological study - Chung, Angeline Kah Yee; Lanisha, Rajendran; Nabil Daniel, Abdul Rahim Chan (2024)
The number of single people around the world is increasing gradually. This shows that singlehood has become a more and more popular trend of lifestyle within society. Although there are some benefits in living as a single person, there are also some. This study is a qualitative study to explore more about singlehood in terms of the meaning, reasons, and challenges behind singlehood. It also highlights some strategies that were implemented to overcome the challenges as extended branch from challenges behind singlehood. Interviews were conducted online and physically among seven single participants who were between 30 – 40 years of age and open-ended questions were asked. Thematic analysis was conducted to analyse the transcripts of interviewees and to create suitable themes based on the research objective. The findings had found several themes which were thoughts and feelings about singlehood, independence, past versus present experiences, personal and lifestyle considerations, individual development and growth, societal pressure, and changes in social life. Limitations of the study were found related with the limited time, diversity of data from different age categories, language barriers, and broad topic. In conclusion, singlehood is a complex mechanism that further research needs to be conducted to understand more about it and, this study could be a potential catalyst for future studies as a point of reference in conducting more thorough research.